PENGARUH KOMPENSASI, BEBAN KERJA DAN PENGEMBANGAN KARIR TERHADAP LOYALITAS KARYAWAN DI RUMAH SAKIT PARU MANGUHARJO MADIUN - Sri Hartono (Jurnal Cakrawala Ilmiah, 2023)
Devi Farma Magetan Pharmacy was influenced by compensation, workload, and career development. This study aims to determine how the effect of compensation, workload and career development on Rumah Sakit Paru Manguharjo Madiun . this research uses descriptive method involving 35 respondents. Data collection is done by using questionnaires. The data obtained were analyzed using statistical formulas, then an analysis of the data obtained was in the form of quantitative analysis includes validity and reliability, hypothesis testing, through the F test and T test and correlation analysis. The data analysis technique used is multiple linear regression analysis that serves to prove the research hypothesis. The results of the descriptive analysis showed that, the factors consisting of compensation, workload, and career developments had an effect on the loyalty of Rumah Sakit Paru Manguharjo Madiun . the results of multiple regression analysis show that career developments factor is the most dominant variable affecting Rumah Sakit Paru Manguharjo Madiun.